Estudio de la funcionalidad hepática relacionado con la dieta en caninos atendidos en la consulta de la clínica veterinaria Vivet. - Peña Granda, Diana Carolina (2022)
The liver is a multifunctional organ, responsible for metabolizing, transporting and storing various substances, for this reason, is subject to multiple actions that can damage its integrity, Therefore, the study of liver functionality through serum chemistry tests is essential. The canine population has increased considerably, and with this the need to deepen the importance of the clinical examination on a regular basis, as well as the nutritional requirements of pets according to their weight and age. The present study aimed to determine the frequency of liver alterations in canines through the analysis of biochemical indicators (urea, total proteins, albumin, ALT, AST, GGT, alkaline phosphatase, total and direct bilirubin) in 30 canines treated at the Vivet Veterinary Clinic in the city of Loja (period November 2020 - January 2021). Possible factors associated with the alteration of liver function to the variables: weight, age and type of feeding were considered. Fisher’s Exact Test was applied to determine the association between the variables, considering p values less than or equal to 0.05 as statistically significant. 40% of the patients studied had at least one analyte of liver function outside the normal range, and the age variable if it represents a risk factor for the presence of liver alteration (p = 0.04921). Keywords: liver, serum chemistry, veterinary, canines, analytes